Pendampingan Kesiapan Mental Belajar Siswa Pada Masa New Normal Di SD Negeri 07 Kota Bengkulu - Susanto, Edy; Martiani; Banat , Azizatul; Febrianti , Mariska; Sumantri , Ajis; Mayulia , Yuyun (Universitas Dehasen Bengkulu, 2021)
Community Service Activities aim to be able to provide new experience and knowledge to teachers and students of SD Negeri 07 in the application of online and face-to-face learning (blended learning) in the new normal period so that existing learning can be used properly and optimally. Based on the results of the Community Service activity entitled